Resubmission of VO#12 valuation for dam proofing works in Raft, Pile cap, H-steel and King post - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding resubmission of VO#12 valuation for dam proofing works in Raft, Pile cap, H-steel and King post of BRAC University new campus project.